2013
DOI: 10.1021/jp310013z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Graphdiyne Probed by X-ray Absorption Spectroscopy and Scanning Transmission X-ray Microscopy

Abstract: The electronic structure of graphdiyne exposed to air is investigated utilizing X-ray absorption spectroscopy and scanning transmission X-ray microscopy. It is found that carbon−carbon triple bonds at defect sites in graphdiyne have been changed to double bonds after 3 months in air. The experimental results reveal the existence of oxygen and nitrogen functional groups and indicate that the oxidation takes place throughout the aged graphdiyne while the nitrogen contamination is mainly on its surface. Buckling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 21 publications
6
80
0
Order By: Relevance
“…1‐Indanone and their derivatives have been extensively studied recently and have shown very good biological activity as anti‐inflammatory, anti‐cancer, antiviral, and antibacterial . Studies carried out on compounds possessing 1‐indanone moiety demonstrated a very potent anti‐inflammatory activity in RAW 264.7 macrophages and inhibiting NO production up to 61% . Thereafter, in the quest to discover valuable anti‐inflammatory compounds, our research groups have performed some synthetic modifications of chalcone to 2‐benzylidene‐1‐indanone (Figure (c)) and 3‐benzylidenechroman‐4‐ones derivatives that inhibited the production of ROS in LPS‐stimulated RAW 264.7 macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…1‐Indanone and their derivatives have been extensively studied recently and have shown very good biological activity as anti‐inflammatory, anti‐cancer, antiviral, and antibacterial . Studies carried out on compounds possessing 1‐indanone moiety demonstrated a very potent anti‐inflammatory activity in RAW 264.7 macrophages and inhibiting NO production up to 61% . Thereafter, in the quest to discover valuable anti‐inflammatory compounds, our research groups have performed some synthetic modifications of chalcone to 2‐benzylidene‐1‐indanone (Figure (c)) and 3‐benzylidenechroman‐4‐ones derivatives that inhibited the production of ROS in LPS‐stimulated RAW 264.7 macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Previously reported L-cysteine-assisted synthesis strategies involving solvothermal processes include Bi 2 S 3 , In 2 S 3 , CuS, PbS, AgBiS 2 , TiO 2 , ZnIn 2 S 4 , Cu 2 CoSnS 4 and CuInS 2 nanocrystals. 17,[23][24][25][26][27][28][29][30][31] CuInS 2 nanocrystals have been synthesized by Liu et al via a L-cysteine-assisted solvothermal process. 17 They obtained a product containing agglomerations of irregular microspheres and nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the removal of these toxic compounds is necessary before the wastewater is sent to the biological treatment unit. A number of treatment technologies have been suggested for PRW that include enhanced photo‐degradation, biodegradation, membrane bioreactor, flocculation and ceramic membrane filtration, advanced oxidation, adsorption, and electrochemical methods …”
Section: Introductionmentioning
confidence: 99%